THE ROLE OF ATTACHMENT IN EMIGRANTS TOURISM DESTINATION CHOICE: A PERSPECTIVE ON ETHNIC TOURISM - Bruno Sousa; Rossana Santos; Diana Azevedo (Enlightening Tourism: A Pathmaking Journal)
Over the years, the emigration of Portuguese population has been a constant debate, reaching large percentages in certain periods of Portuguese history. This phenomenon has had a significant impact in areas such as economy, demography, culture, among many others, visible at national, regional and local levels. Emigrants become Portuguese communities residing outside the country, and emigration generates the emergence of the Portuguese diaspora. The phenomenon of emigration involves the bilateral focus between the country of origin and the country of destination. Therefore, the affection component assumes special importance in tourism studies and decision making by visitors and tourists (e.g. behavioural intentions). In this study, a preliminary contribution is presented based on a sample of 1057 respondents (i.e. Portuguese residing abroad), aiming to better understand and analyse the profile of migrants and what motivates them to return to Portugal in contexts of tourism and leisure. More than 50% of respondents report visiting their home country (Portugal) at least once a year (i.e. ethnic tourism). Therefore, a conceptual model is presented, which seeks to highlight the role of attachment on emigrants` behavioural intensities (i.e. choosing the tourist destination Portugal). The results show that attachment influences the decision of emigrants to choose Portugal as a holiday destination, namely with regard to satisfaction and loyalty to the destination (revisit and recommendation). In the end, conclusions and limitations of the study will be presented and guidelines for future research will be discussed.